2023
DOI: 10.3390/su151310720
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Spatial Structure and Drivers of Agricultural Carbon Emission Efficiency in Belt and Road Initiative Countries

Abstract: Agricultural carbon emissions are one of the major causes of global climate change. As some of the world’s largest agricultural producers and consumers, countries along the route of the Belt and Road initiative produce significant agricultural carbon emissions. An in-depth study on the efficiency of agricultural carbon emissions in countries along the route can help countries reduce environmental load while improving agricultural production, optimizing resource use, improving agricultural production efficiency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…With regard to methodology, the ACEE is usually measured by Malmquist [32] and DEA [33]. Currently, scholars' studies on the ACEE include the evaluation indexes [34], influences [35], and the decoupling effect from economic growth [36].…”
Section: Introductionmentioning
confidence: 99%
“…With regard to methodology, the ACEE is usually measured by Malmquist [32] and DEA [33]. Currently, scholars' studies on the ACEE include the evaluation indexes [34], influences [35], and the decoupling effect from economic growth [36].…”
Section: Introductionmentioning
confidence: 99%
“…When analyzing the spatial correlation of carbon emission, scholars used various methods, including global spatial autocorrelation Moran's I index, local spatial autocorrelation Moran's I index, and aggregation map, to conduct exploratory spatial data analysis (ESDA) in different research areas, and then concluded that regional carbon emissions exhibit significant spatial correlation [1][2][3][4][5]. Considering the intricate nonlinear network relationships inherent in regional carbon emissions, scholars used Social Network Analysis (SNA) to construct spatial correlation networks, analyzing overall network characteristics [6,7] and individual network characteristics [8,9]. In addition, scholars used the iterative correlation convergence method (CONCOR) for spatial clustering analysis [10,11].…”
Section: Introductionmentioning
confidence: 99%